Determinantes estruturais da bioluminescência vermelha e eficiência catalítica na luciferase de phrixothrix hirtus e seleção de combinação emissora de luz vermelha distante com 6´-amino-análogos de luciferina - Bevilaqua, Vanessa Rezende (2019)
Luciferases are the enzymes responsible for bioluminescence. These enzymes catalyze the oxidation of luciferins, in which the energy is released in the form of light with high efficiency. The luciferases fireflies from North America, Europe and Japan are the most known and have been the most used for analytical porpouses, however, they have limited applicability in mammalian tissue bioimaging, because its structure is adapted to the production of yellow-green bioluminescence, which is partially absorbed by hemoglobin and bone tissues. The Phrixothrix hirtus railroadworm luciferase, cloned and characterized by our group, is the only one that naturally produces red light, has a high affinity for luciferin and a reasonable affinity for ATP, being potentially useful for analytical assays and pigmented samples. However, the wild-type luciferase has low quantum yield (15%) and thermoestability when compared to green light-emitting luciferases (40 to 60%). In order to better understand the relationship between the structure and activity and bioluminescence spectrum in this luciferase, and then to develop brighter and red- shifted luciferase, site-directed mutagenesis were performed in the active site and investigated the 6' amino analogues effect in the bioluminescence properties. The majority of luciferin binding site mutations impacted catalytic properties, including KM, both overall and oxidative constant and efficiency, but did not affect the spectrum significantly, indicating that these active site residues are important for luciferin binding and catalytic activity, but do not interact with the excited oxyluciferin during the light emission step. The only mutations that affected the spectra are located on the benzothiazolic side of the luciferin binding site. Thus, to better understand the influence and interectaions of this benzothiazolic side of the luciferin binding site in the bioluminescent properties, we used luciferin amino-analogues modified in 6'-position. The P. hirtus red-emitting luciferase had the highest bioluminescent activity and the most far red-shifted spectra with larger 6 'amino-analogs than other luciferases, indicating a larger cavity on the benzothiazolic side of the luciferin binding site. Modeling and site-directed mutagenesis, showed that the cavity created by the L348 residue is critical for red light emission. Finally, the combination of Phrixotrix red light-emitting luciferase and Pyrrolidinyl-luciferin analogue produced far red emission (645 nm) with high activity, promising for bioimaging use of hemoglobin cells and tissues.